Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1093/jae/12.4.564
|View full text |Cite
|
Sign up to set email alerts
|

Urban-Rural Inequality in Living Standards in Africa

Abstract: In this paper we examine the relative importance of rural versus urban areas in terms of monetary poverty and seven other related living standards indicators. We present the levels of urban-rural differences for several African countries for which we have data and find that living standards in rural areas lag far behind those in urban areas. Then we examine the relative and absolute rates of change for urban and rural areas and find no overall evidence of declining differences in the gaps between urban and rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(117 citation statements)
references
References 17 publications
7
110
0
Order By: Relevance
“…Also, Ancharaz (2003) shows that higher urbanization shares increase the likelihood of trade policy reform, and moreover, see Sahn and Stifel (2003), the welfare level of the urban population is generally higher than that of the rural population in SSA, resulting in higher demand for imported manufacturing products. Finally, we also include dummies for intra-SSA and internal trade (α ssa , α own )…”
mentioning
confidence: 99%
“…Also, Ancharaz (2003) shows that higher urbanization shares increase the likelihood of trade policy reform, and moreover, see Sahn and Stifel (2003), the welfare level of the urban population is generally higher than that of the rural population in SSA, resulting in higher demand for imported manufacturing products. Finally, we also include dummies for intra-SSA and internal trade (α ssa , α own )…”
mentioning
confidence: 99%
“…Although the RAI findings do not provide an indication of the conditions of rural roads and demographics characteristics of each country, they provide a comparative overview of rural accessibility in selected African countries. The above findings become extremely important in understanding socioeconomic conditions of rural communities since studies indicate that more than half of the population in Africa still resides in rural areas (Sahn and Stifel, 2003, Cohen, 2006and Beegle et al 2016). …”
Section: Overview Of Rural Roads In South Africamentioning
confidence: 93%
“…In Africa, Sahn and Stifel (2003) found that the population living below the poverty line is about 50% greater in rural areas than in urban areas. They attribute most of these differences to a skewed distribution of schools and health care facilities that favor urban centers.…”
Section: Fiscal Policy and Inequality: Cross-country Evidencementioning
confidence: 99%